Global Tobacco Tapestry: Unraveling the Interdependencies and Drivers of Unmanufactured Tobacco Imports - Ati Kusmiati; Rena Yunita Rahman; Rizky Yanuarti; Titin Agustina; Ebban Bagus Kuntadi; Agus Supriono; Shafira Salsabila (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
Indonesia holds significant potential in both domestic and international tobacco markets, ranking as the world's fourth-largest producer after China, India, and Brazil. However, unmanufactured tobacco (HS 2401) exports lag imports, potentially impacting the economy negatively. This study analyzes the dependency, openness, and characteristics of Indonesia's tobacco imports over a 10-year period (2014-2023), alongside the factors influencing import volumes from 1992 to 2022. Secondary data was sourced from the Central Statistics Agency (BPS), UN Comtrade, FAO, and the Ministry of Agriculture. Analytical methods included the Import Dependency Ratio (IDR), Self-Sufficiency Ratio (SSR), Trade Specialization Index (TSI), Import Openness Degree (IOD), Geographic Concentration Degree (GCD), and multiple linear regression. The results reveal an average IDR of 26.96% and an SSR of 73.04%, indicating that 26.96% of tobacco demand is met through imports, while 73.04% is fulfilled domestically. The average TSI value of -0.55 signifies Indonesia as a net importer. The average import openness (IOD) was 0.06% of GDP during 2014-2023. International tobacco prices and domestic demand significantly influenced import volumes, whereas domestic production and prices showed no significant impact. The Indonesian cigarette industry exhibits high import dependence due to domestic production not yet meeting required quantity and quality standards. Recommendations include enhancing tobacco quantity and quality through Good Agricultural Practices (GAP) implementation, providing comprehensive support for developing industry-aligned tobacco, and ratifying the Framework Convention on Tobacco Control (FCTC) to reduce tobacco consumption and imports.